2013 Congo, Dem. Rep. Enterprise Survey : Country Highlights - World Bank Group (Washington, DC, 2014)
The World Bank interviewed a representative sample of the private sector, composed of 529 establishments, between August 2013 and May 2014. The Enterprise Survey covers several aspects of the business environment as well as performance measures for each firm.